2018
DOI: 10.1017/s0031182018001397
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolyticainfection in humans, chimpanzees and baboons in the Greater Gombe Ecosystem, Tanzania

Abstract: Entamoeba histolytica is an enteric parasite that infects approximately 50 million people worldwide. Although E. histolytica is a zoonotic parasite that has the potential to infect nonhuman primates, such transmission is poorly understood. Consequently, this study examined whether E. histolytica is present among humans, chimpanzees and baboons living in the Greater Gombe Ecosystem (GGE), Tanzania. The primary aims were to determine patterns of E. histolytica infection in a system with human-nonhuman primate ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
1
24
3
Order By: Relevance
“…Our results reject the hypothesis that orangutans are not infected with E. histolytica as we confirm for the first time that orangutans in the wild are infected with this pathogenic species of Entamoeba . We do so by confirming infection by PCR assays specific to E. histolytica and the sequences obtained showing a higher concordance to E. histolytica than E. dispar or E. nuttalli (Deere et al, 2018; Fotedar et al, 2007; Robertson et al, 2019).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our results reject the hypothesis that orangutans are not infected with E. histolytica as we confirm for the first time that orangutans in the wild are infected with this pathogenic species of Entamoeba . We do so by confirming infection by PCR assays specific to E. histolytica and the sequences obtained showing a higher concordance to E. histolytica than E. dispar or E. nuttalli (Deere et al, 2018; Fotedar et al, 2007; Robertson et al, 2019).…”
Section: Discussionsupporting
confidence: 64%
“…dispar , since they have been identified using only microscopy (Nurcahyo et al, 2017). The majority of studies of Entamoeba species infecting NHPs using molecular techniques have failed to detect E. histolytica , though often they found E. dispar (Feng et al, 2011, 2013; Jirků‐Pomajbíková et al, 2016; Rivera & Kanbara, 1999; Tachibana, Cheng, Kobayashi, Fujita, & Udono, 2000; Tachibana et al, 2001); recently E. histolytica has been identified in baboons, chimpanzees, and gorillas (Deere et al, 2018; Vlčková et al, 2018). Also, Entamoeba nuttalli , was discovered, which is closely related to E. histolytica (Tachibana et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in an anthropogenic habitat will cause humans and nonhuman primates to have frequent contact leading to an increased risk of disease transmission [22]. A recent study conducted in the Greater Gombe Ecosystem, Tanzania, has confirmed the risk of zoonotic transmission of Entamoeba histolytica [23]. Identifying Entamoeba histolytica/dispar in the baboon faecal samples from Shai Hills Reserve indicates a need to access the potential zoonotic transmission to individuals in the surrounding communities.…”
Section: Discussionmentioning
confidence: 99%
“…Several examples show the potential for bidirectional cross-species pathogen transmission. In samples of nearly 300 for each host species, Entamoeba enteric species were detected in 66% of chimpanzees and 60% of humans within the Gombe ecosystem, while the diarrheacausing Entamoeba histolytica was in 34% of chimpanzees and 12% of humans (Deere et al 2019). Respiratory viruses in Kibale chimpanzees show human origins: metapneumovirus (MPV), respiratory syncytial virus (RSV), and rhinovirus-C (RV-C; Emery .…”
Section: Bipedality Lung Evolution and Aerosol Exposuresmentioning
confidence: 99%